Pondok Persulukan dan Manajemen Perubahan - Hasibuan, Armyn (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2023)
AbstractThe purpose of this article is to provide an idea of renewal at the level of local wisdom in the Pondok  Persulukan in Tabagsel (South Tapanuli) so that in the practice of tasawuf tarekat using change management effectively and efficiently, not only relying on tradition and negating what has been passed down from generation to generation. Good management includes conceptual and action that can be tested as standard operating procedures (SOP). Tasawuf tarekat as part of Islamic teachings that are in the corridor of zany al-Dhilalah should be able to accept modernity such as the application of digital which greatly helps sheikhs, murshids, caliphs, founders, heads of foundations or other executors in storing data on tarekat students, the ins and outs of correspondence, let alone practicing the elements of management that should exist in the world of persulukan starting from designing, organizing, implementing, supervising to evaluating even though it is a non-formal educational institution. In the area of South Tapanuli (Tabagsel), almost all of the Tariqah shaykhs have not implemented a good managerial system in the Pondok Persulukan that they foster, seeming monotonous, static and not developing as expected, even though management in it is found in the arrangement of data and administration which is very important in the development of educational institutions in responding to contemporary life today. Allah Swt. also likes order, neatness and order that is beautifully arranged like an army in a prade line or like a neatly arranged and sturdy building. Many Quranic verses are related to management either explicitly or implicitly as found in Q.S.10:1 and 31, Q.S.13:2 and Q.S. 33: 5. Likewise, the hadith of the Prophet Saw. about leadership management that every leader will be held accountable which is interpreted broadly including how governance as an inseparable part of leadership and its work. Abstrak                Tujuan artikel ini memberikan ide pembaruan setingkat kearifan local pada pondok persulukan di Tabagsel  (Tapanuli Bagian Selatan) agar dalam praktik tasawuf tarekat memakai manajemen perubahan secara efektif dan efesien, tidak hanya mengandalkan tradisi dan memadakan apa yang ada secara turun temurun. Manajemen yang baik terdapatnya konseptual dan action yang dapat diuji coba sebagai standar operasional prosedur (SOP). Tasawuf tarekat sebagai bagian dari ajaran islam yang berada dalam koridor zany al-Dhilalah seharusnya dapat menerima modernitas seperti penerapan digital yang amat membantu syekh, mursyid, khalifah, pendiri, ketua yayasan atau pelaksana lainnya dalam menyimpan data data murid tarekat, seluk beluk persuratan apalagi memperaktekkan unsur unsur manajemen sudah selayaknya ada dalam dunia persulukan mulai perancangan, pengorganisasian, pelaksanaan, pengawasan sampai pengevaluasian meskipun sebagai lembaga pendidikan non formal. Di daerah Tapanuli Bagian Selatan (Tabagsel) hampir semua para syekh tarekat belum melaksanakan manajerial yang baik di pondok persulukan yang mereka asuh, terkesan monoton, statis dan tidak berkembang sesuai harapan, padahal manajemen di dalamnya ditemui penataan data data dan administrasi yang amat penting dalam perkembangan lembaga pendidikan dalam menyahuti kehidupan kontemporer dewasa ini. Allah Swt. juga senang kepada ketertiban, kerapian dan keteraturan yang tertata dengan indah bagaikan tentara dalam barisan prade atau bagaikan bangunan tersusun rapi dan kokoh. Banyak ayat alquran yang berkaitan manajemen baik secara eksplisit maupun implicit seperti terdapat pada Q.S.10/Yunus:31, Q.S.13/Arra’d:2 dan Q.S. 33 Al-Ahzab: 5. Demikian juga hadis Rasul Saw. tentang menanejemen kepemimpinan bahwa setiap pemimpin akan diminta pertanggung jawabannya yang dimaknai secara luas termasuk di dalamnya bagaimana tata kelola sebagai bagian takterpisahkan dari kepemimpinan dan pekerjaannya itu